Risk Factors for Suicidality in Pregnant Women in Nigeria - Azizat Abiodun Lebimoyo; Mujeedat Aderinola Hassan (Taiwanese Journal of Psychiatry)
Objectives: Globally, antepartum suicidality is a prominent mental health morbidity reported by pregnant women, with a potential to cause adverse consequences in affected women not only during antepartum but also in the postpartum period. Some contextual factors are known to initiate and perpetuate suicidality in pregnancy. Currently, there are sparse studies concerning suicidality and its related factors among Nigerian pregnant women. In this study, we intended to determine the prevalence and risk factors of antepartum suicidality among pregnant women attending an antenatal clinic at a teaching hospital in Lagos, in southwestern Nigeria. Methods: This was a cross-sectional descriptive study of 116 pregnant women recruited using systematic random sampling. The instruments used were the Suicide Behavior Questionnaire-Revised, Postpartum Depression Predictors Inventory-Revised (Prenatal Version), Abuse Assessment Screen, and a copy of Sociodemographic and Clinical Data Questionnaire. Results: The prevalence of antepartum suicidality was 29.3%. We found that significant risk factors of suicidality were income (p = 0.01), intimate partner violence (p = 0.001), use of assisted reproductive technique (p =0.01), depression (p = 0.001), and family history of suicide (p = 0.01). Conclusion: The occurrence of suicidal thoughts and behaviors in pregnant women may be influenced by diverse clinical and psychosocial factors. There is a need to establish services and programs which encourage maternal mental health promotion, suicide behavior prevention, and suicide risk reduction among pregnant women in Nigeria.